Local and Systemic Cytokine Expression in Patients with Postherpetic Neuralgia - Üçeyler, Nurcan (Public Library of Science, 2014)
BACKGROUND: Postherpetic neuralgia (PHN) is the painful complication of a varicella zoster virus reactivation. We investigated the systemic and local gene expression of pro- and anti-inflammatory cytokine expression in patients with PHN. METHODS: Thirteen patients with PHN at the torso (Th4-S1) were recruited. Skin punch biopsies were obtained from the painful and the contralateral painless body area for intraepidermal nerve fiber density (IENFD) and cytokine profiling. Additionally, blood was withdrawn for systemic cytokine expression and compared to blood values of healthy controls. We analyzed the gene expression of selected pro- and anti-inflammatory cytokines (tumor necrosis factor-alpha [TNF] and interleukins [IL]-1β, IL-2, and IL-8). RESULTS: IENFD was lower in affected skin compared to unaffected skin (p<0.05), while local gene expression of pro- and anti-inflammatory cytokines did not differ except for two patients who had 7fold higher IL-6 and 10fold higher IL-10 gene expression in the affected skin compared to the contralateral unaffected skin sample. Also, the systemic expression of cytokines in patients with PHN and in healthy controls was similar. CONCLUSION: While the systemic and local expression of the investigated pro- and anti-inflammatory cytokines was not different from controls, this may have been influenced by study limitations like the low number of patients and different disease durations. Furthermore, other cytokines or pain mediators need to be considered.